Gene Therapy for Mucopolysaccharidosis Type VI Is Effective in Cats Without Pre-Existing Immunity to AAV8 - Ferla, Rita (Mary Ann Liebert, Inc., 2013)
Liver gene transfer with adeno-associated viral (AAV) 2/8 vectors is being considered for therapy of systemic diseases like mucopolysaccharidosis type VI (MPS VI), a lysosomal storage disease due to deficiency of arylsulfatase B (ARSB). We have previously reported that liver gene transfer with AAV2/8 results in sustained yet variable expression of ARSB. We hypothesized that the variability we observed could be due to pre-existing immunity to wild-type AAV8. To test this, we compared the levels of AAV2/8-mediated transduction in MPS VI cats with and without pre-existing immunity to AAV8. In addition, since levels of lysosomal enzymes as low as 5% of normal are expected to be therapeutic, we evaluated the impact of pre-existing immunity on MPS VI phenotypic rescue. AAV2/8 administration to MPS VI cats without pre-existing neutralizing antibodies to AAV8 resulted in consistent and dose-dependent expression of ARSB, urinary glycosaminoglycan (GAG) reduction, and femur length amelioration. Conversely, animals with pre-existing immunity to AAV8 showed low levels of ARSB expression and limited phenotypic improvement. Our data support the use of AAV2/8-mediated gene transfer for MPS VI and other systemic diseases, and highlight that pre-existing immunity to AAV8 should be considered in determining subject eligibility for therapy.